Severe hematoma following the use of low molecular weight heparin in preterm neonate - Dr. Naveed Ur Rehman Durrani (18262147) (2022)
Objectives With the increased survival of preterm neonates, thromboembolic (TE) events are increasingly being recognized due to the use of indwelling catheters. It is still debatable to treat TE with low molecular weight heparin (LMWH) or follow expectant management. Despite the safety and efficacy profile about using LMWH in adults, its use in extreme preterm neonates with TE events is limited. The therapeutic level and pharmacokinetics of LMWH in the preterm population are relatively variable. Case presentation We present a case with a severe hematoma on the left thigh following the use of LMWH, which was surgically drained and had a successful skin graft. Conclusions This case highlights the importance of early and close monitoring of injection sites in patients treated with LMWH. Other Information Published in: Case Reports in Perinatal Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/crpm-2021-0086